Microbes, Clinical trials, Drug Discovery, and Vaccine Development: The Current Perspectives - Venkataramana Kandi; Tarun Kumar Suvvari; Sabitha Vadakedath; Vikram Godishala (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Because of the frequent emergence of novel microbial species and the re-emergence of genetic variants of hitherto known microbes, the global healthcare system, and human health has been thrown into jeopardy. Also, certain microbes that possess the ability to develop multi-drug resistance (MDR) have limited the treatment options in cases of serious infections, and increased hospital and treatment costs, and associated morbidity and mortality. The recent discovery of the novel Coronavirus (n-CoV), the Severe Acute Respiratory Syndrome CoV-2 (SARS-CoV-2) that is causing the CoV Disease-19 (COVID-19) has resulted in severe morbidity and mortality throughout the world affecting normal human lives. The major concern with the current pandemic is the non-availability of specific drugs and an incomplete understanding of the pathobiology of the virus. It is therefore important for pharmaceutical establishments to envisage the discovery of therapeutic interventions and potential vaccines against the novel and MDR microbes. Therefore, this review is attempted to update and explore the current perspectives in microbes, clinical research, drug discovery, and vaccine development to effectively combat the emerging novel and re-emerging genetic variants of microbes.